A preparation method for hierarchical porous collagen-based metal nickel organic framework composite carbon nanofiber fuel cell cathode material

By using white powder and bayberry tannin to modify the modified metal-organic frame composite material MOF-74@CCF-BT, the problems such as high synthesis cost of fuel cell catalysts and toxicity of platinum-based catalytic materials are solved, and efficient catalytic effect of redox reactions is achieved.

CN115440992BInactive Publication Date: 2025-02-28FUZHOU UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211117723.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-14
Publication Date
2025-02-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing fuel cell catalysts have problems such as single obstacles in precursors, high synthesis costs, high cost and toxicity of platinum-based catalytic materials.

Method used

The catalyst is synthesized through a simple thermal decomposition preparation process using collagen fibers, a modified graded porous collagen-based metal nickel organic frame composite carbon nanofiber MOF-74@CCF-BT nanomaterial using collagen fibers, using the interface adhesion of bayberry tannin.

Benefits of technology

The catalyst has high starting potential, half slope potential, excellent limit current, excellent stability and methanol tolerance, which is superior to traditional Pt/C catalysts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115440992B_ABST
    Figure CN115440992B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of fuel cell electrode materials, and specifically relates to a method of using collagen fibers, the main component of white skin powder, as a substrate and using the interface adhesion modification of bayberry tannin to construct a hierarchical porous skin collagen-based metal nickel organic framework composite carbon nanofiber MOF‑74@CCF‑BT. The synthesis method is simple, low in cost, high in yield, large in specific surface area, and easy to realize industrial production. The invention is used to solve the problems of single precursor, high cost, low exchange current density, etc. in existing fuel cell electrodes, and the obtained oxygen reduction electrocatalyst has the advantages of high starting potential, half-slope potential, limiting current, high stability, and strong resistance to methanol poisoning. Therefore, using biomass skin powder as a good carrier and carbon source, plant tannin as a bridge molecule connecting collagen fibers and nickel metal organic frameworks, the developed MOF‑74@CCF‑BT has great potential application value and industrialization prospects as a substitute for traditional commercial Pt / C.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of oxygen reduction electrocatalysis, and specifically relates to a method for preparing hierarchical porous skin collagen-based metal nickel organic framework composite carbon nanofibers using collagen fibers, the main component of white skin powder, as a substrate and modified by interface adhesion modification of bayberry tannin. Background Art

[0002] The slow redox reaction process at the cathode has greatly hindered the development of proton exchange membrane fuel cells (PEMFCs), and an efficient catalyst is needed for catalysis. The traditional method for preparing redox electrocatalysts is the template method, which involves the preparation and removal of templates. The template is generally etched with hydrofluoric acid (HF), and HF is a highly corrosive acid. The operation during the synthesis process is highly dangerous and will pollute the environment. At present, in order to improve the reaction kinetics of the redox reaction (ORR) on the cathode electrode, a large amount of expensive platinum-based electrocatalysts is required to improve this performance. However, the high price, scarcity, durability, and poor toxicity of platinum have hindered the practical application prospects of fuel cell systems. Therefore, the development of highly active non-precious metal redox reaction catalysts is one of the core steps to achieve the commercialization of fuel cells.

[0003] Tannins are secondary metabolites of plants and widely exist in the roots, skins, leaves and fruits of plants. They are natural polyphenol compounds. Tannins are divided into hydrolyzable tannins and condensed tannins. Hydrolyzable tannins refer to tannins of citric acid (gallic acid) or galactoic acid produced by hydrolysis under the action of acid, alkali or enzymes, such as tannic acid and tara tannin; while condensed tannins are generally derived from flavanol compounds, which are polymers of flavan-3-ol or flavan-3,4-diol, such as black wattle tannin, bayberry tannin and larch tannin. Bayberry tannin has multiple ortho-phenolic hydroxyl groups, which enable it to undergo electrostatic binding and complexation reactions with a variety of metal ions. The former is mainly a physical process, while the latter is a chemical process. Tannins mainly form five-membered chelates with metal ions through ortho-diphenolic hydroxyl groups, and other reactions such as redox and hydrolysis coordination may also occur at the same time.

[0004] Metals and organic compounds coordinate to form a specific framework structure, which not only has the activity of metals, but also has the characteristics of organic ligands, functional group selectivity and other physical and chemical properties, as well as a special spatial structure formed by coordination. Metal-organic framework (MOFs) materials have the advantages of simple preparation, low production cost, large surface area, large pore volume and easy manufacturing, which also enables them to load guest molecules and directly catalyze target substances, thereby providing more active sites and improving the sensitivity of electrochemical detection. Therefore, it is of great significance to select different metal centers and organic linkers to synthesize target molecules with specific structures, thereby producing functional materials with both metal properties and organic properties, which is of great significance to improving electrochemical performance.

[0005] Hide collagen fibers are derived from the skins of livestock animals and are the most abundant renewable animal biomass in nature. The theory and practice of inorganic metal salt tanning in the field of leather chemistry have confirmed that hide collagen can cross-link with metal ions. A large number of functional groups, such as -COOH, -NH2, -OH, etc., are regularly distributed in the molecular structure of collagen fibers. These active groups can coordinate with metal ions to fix the metal ions on the collagen fibers. This article uses MOF-74, a metal organic framework (MOFs) material with open, high-density unsaturated and metal sites. It is composed of Ni 2+ A three-dimensional network skeleton material with one-dimensional channels obtained by coordinating metal ions with 2,5-dihydroxyterephthalic acid. MOF-74 and bayberry tannin are combined with leather powder for modification to obtain a composite material with large specific surface area and high activity to replace the traditional Pt / C catalyst. Summary of the invention

[0006] The purpose of the present invention is to solve the problems existing in existing fuel cell catalysts and overcome the defects of the prior art. At present, fuel cell catalysts generally face the obstacles of a single precursor and the problem of synthesis cost, as well as the defects of high cost and toxicity of platinum-based catalytic materials. By utilizing the characteristics of metal organic frameworks with multiple active sites and a large specific surface area, a nanocomposite material is developed that combines MOFs and bayberry tannins and is modified with skin powder. The nanocomposite material has the advantages of high starting potential, half-slope potential, excellent limiting current, excellent stability and methanol tolerance.

[0007] The invention provides a simple thermal decomposition preparation process for synthesizing a hierarchical porous collagen-based metal nickel organic framework composite carbon nanofiber MOF-74@C, which is based on collagen fibers, the main component of white peel powder, and modified by interface adhesion of bayberry tannin. CF-BT , the steps are as follows:

[0008] (1) Prepare a certain ratio of DMF-ethanol-ultrapure water solution;

[0009] (2) 0.1473 g H4DOBDC and 0.7718 g Ni(NO3)2·6H2O were dissolved in the above solution, and then transferred into a 100 ml hydrothermal reactor and maintained at a certain temperature. After a period of time, the reaction was completed and cooled to room temperature. The obtained solid was washed with DMF and methanol three times respectively, and finally vacuum dried under certain conditions to obtain Ni-MOF-74;

[0010] (3) Weigh 0.05 g of skin powder and dissolve it in 10 ml of deionized water. Add 10% HCl solution to adjust the pH, and then shake it at 40°C for 2 h.

[0011] (4) Weigh 0.05 g MOF-74 and 0.1 g bayberry tannin respectively and dissolve them in the conical flask in step (3), stir them with a magnetic stirrer, and then shake them on an oscillator;

[0012] (5) After sufficient shaking, wash with deionized water and anhydrous ethanol 2 to 3 times, filter and dry in an oven;

[0013] (6) The dried product was placed in a tubular furnace in a nitrogen atmosphere for heat treatment, and then naturally cooled to room temperature to obtain a hierarchical porous collagen-based metal nickel organic framework composite carbon nanofiber MOF-74@C with collagen fibers as the main component of white peel powder as the base material and modified by the interface adhesion of bayberry tannin. CF-BT Nanomaterials.

[0014] In the above technical scheme, the volume ratio of DMF-ethanol-ultrapure water in step (1) is 1:1:1, a total of 60 ml;

[0015] In the above technical solution, the temperature of the hydrothermal reaction in step (2) is 100°C, the time is 24 h, and the temperature of the vacuum drying is 80°C, the time is 12 h;

[0016] In the above technical solution, the pH range of step (3) is adjusted to 1.5-2.0;

[0017] In the above technical solution, the magnetic stirring time in step (4) is 30 minutes, the oscillator temperature is 40°C, and the time is 2 hours;

[0018] In the above technical solution, the drying temperature in step (5) is 80°C and the time is 12h;

[0019] In the above technical solution, the heat treatment heating rate in step (6) is 5 °C / min, the temperature is 800 °C, and the reaction time is 2 h.

[0020] The MOF-74@C CF-BT Compared with commercial Pt / C catalysts, oxygen reduction reaction catalysts have the following advantages:

[0021] (1) The catalyst preparation process adopts a thermal decomposition method with simple equipment, simple operation steps, green environmental protection, and easily controllable reaction conditions. It not only exhibits high starting potential, half-slope potential, excellent limiting current, excellent stability and good methanol tolerance, but also has strong resistance to methanol poisoning.

[0022] (2) Prepared MOF-74@C CF-BTThe catalyst has an initial potential of 0.88 V relative to the standard hydrogen electrode measured in an electrochemical workstation, which is comparable to Pt / C. The material half-slope potential is 0.78 V, slightly better than Pt / C. At the same time, the catalyst has a higher limiting current density of 5.54 mA cm-2 than Pt / C. -2 . BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The prepared method of Example 1 is a hierarchical porous collagen-based metal nickel organic framework composite carbon nanofiber MOF-74@C with collagen fiber as the main component of white skin powder as the base material and modified by the interface adhesion of bayberry tannin. CF-BT SEM scanning images of

[0024] Figure 2 XRD patterns of MOF-74@BT materials obtained at different calcination temperatures (600 ℃, 700 ℃, 800 ℃) (scanning range: 5°-80°, step length: 0.02°, scanning rate: 1.5° / min);

[0025] Figure 3 The MOF-74@C prepared at 800 °C calcination temperature in Example 1 CF-BT SEM images and EDS spectra of materials;

[0026] Figure 4 The MOF-74@C prepared at 800 °C calcination temperature in Example 1 CF-BT Elements and spectra of materials;

[0027] Figure 5 The MOF-74@C prepared at 800°C calcination temperature in Example 1 CF-BT CV graph of the material in O2-saturated 0.1 MKOH at 1600 rpm (scanning range: -0.9-0.1 V, scan rate: 50 mV / s);

[0028] Figure 6 CV graphs of MOF-74 and bayberry tannin in different proportions at 800°C calcination temperature in Example 1 at 1600 rpm in 0.1M KOH saturated with O2 (scanning range: -0.9-0.1 V, scanning rate: 50 mV / s);

[0029] Figure 7 The control sample Pt / C and the MOF-74@C prepared at 800℃ calcination temperature in Example 1 CF-BT LSV comparison of materials in O2-saturated 0.1 M KOH at 1600 rpm;

[0030] Figure 8Preparation of MOF-74@C at different calcination temperatures (700 ℃, 750 ℃, 800 ℃) CF-BT LSV comparison of materials in O2-saturated 0.1 M KOH at 1600 rpm (scanning range: -0.9-0.1 V, scan rate: 10 mV / s);

[0031] Fig. 9 MOF-74@C with different speeds CF-BT LSV diagram of the material (rotation speed is 400 rpm, 625 rpm, 900 rpm, 1225 rpm, 1600 rpm, 2025 rpm, scanning rate is 10 mV / s);

[0032] Fig.10 The MOF-74@C calcined at 800°C in Example 1 CF-BT Comparison of it curves of the material and commercial Pt / C running at 1600 rpm for a long time in O2-saturated 0.1 M KOH;

[0033] Fig.11 The MOF-74@C calcined at 800°C in Example 1 CF-BT Comparison of IT curves of the material and commercial Pt / C after adding methanol. DETAILED DESCRIPTION

[0034] The simple preparation process provided by the invention uses collagen fibers, the main component of white peel powder, as the base material and utilizes the interface adhesion modification of bayberry tannin to prepare a hierarchical porous skin collagen-based metal nickel organic framework composite carbon nanofiber MOF-74@C CF-BT Used as cathode material for fuel cells, the steps are as follows:

[0035] (1) Prepare a certain ratio of DMF-ethanol-ultrapure water solution;

[0036] (2) 0.1473 g H4DOBDC and 0.7718 g Ni(NO3)2·6H2O were dissolved in the above solution, and then transferred into a 100 ml hydrothermal reactor and maintained at a certain temperature. After a period of time, the reaction was completed and cooled to room temperature. The obtained solid was washed with DMF and methanol three times respectively, and finally vacuum dried under certain conditions to obtain Ni-MOF-74;

[0037] (3) Weigh 0.05 g of skin powder and dissolve it in 10 ml of deionized water. Add 10% HCl solution to adjust the pH, and then shake it at 40°C for 2 h.

[0038] (4) Weigh 0.05 g MOF-74 and 0.1 g bayberry tannin respectively and dissolve them in the conical flask in step (3), stir them with a magnetic stirrer, and then shake them on an oscillator;

[0039] (5) After sufficient shaking, wash with deionized water and anhydrous ethanol 2 to 3 times, filter and dry in an oven;

[0040] (6) The dried product was placed in a tubular furnace in a nitrogen atmosphere for heat treatment, and then naturally cooled to room temperature to obtain a hierarchical porous carbon nanostructured MOF-74@C with the leather powder as a good carrier and carbon source. CF-BT fiber.

[0041] In the above technical scheme, the volume ratio of DMF-ethanol-ultrapure water in step (1) is 1:1:1, a total of 60 ml;

[0042] In the above technical solution, the temperature of the hydrothermal reaction in step (2) is 100°C, the time is 24 h, and the temperature of the vacuum drying is 80°C, the time is 12 h;

[0043] In the above technical solution, the pH range of step (3) is adjusted to 1.5-2.0;

[0044] In the above technical solution, the magnetic stirring time in step (4) is 30 minutes, the oscillator temperature is 40°C, and the time is 2 hours;

[0045] In the above technical solution, the drying temperature in step (5) is 80°C and the time is 12h;

[0046] In the above technical solution, the heat treatment heating rate in step (6) is 5 °C / min, the temperature is 800 °C, and the reaction time is 2 h.

[0047] The invention provides a nano composite material MOF-74@C synthesized by using leather powder as a modification and a metal organic framework polyphenol supramolecular network as a functional assembly. CF-BT And use this material as an oxygen reduction catalyst.

[0048] The active material described in the present invention is abbreviated as MOF-74@C CF-BT .

[0049] The MOF-74@C of the present invention CF-BT The material is a hierarchical porous skin collagen-based metal nickel organic framework composite carbon nanofiber, which is modified by using collagen fibers, the main component of white skin powder, as the base material and using the interface adhesion modification of bayberry tannin.

[0050] The present invention uses a platinum electrode as a counter electrode, a saturated silver chloride electrode (Ag / AgCl) as a reference electrode, and MOF-74@CCF-BT The platinum-carbon electrode made of the composite material was used as the working electrode.

[0051] 4 mg of the catalyst of the present invention was weighed on a balance and dispersed in 1 mL of a mixed solution (235 μL of deionized water, 750 μL of isopropanol and 15 μL of 5 wt% Nafion solution) to prepare a catalyst ink. Then 28 μL of the ink was gradually added dropwise to the surface of the glassy carbon electrode (catalyst loading 0.25 mg cm -2 ), and then the electrocatalytic performance was tested after natural drying.

[0052] All the electrocatalytic performance tests described in the present invention are carried out in 0.1 M KOH (pH = 13.62) electrolyte, and the potential measured in the experiment can be converted to the potential relative to the reversible hydrogen electrode (RHE) by the following formula:

[0053]

[0054] The potential values ​​involved in the present invention are all potentials relative to a reversible hydrogen electrode.

[0055] The catalyst of the present invention needs to be activated by CV for 3 cycles before electrochemical testing.

[0056] The catalysts described in the present invention are all tested at room temperature to prevent large temperature changes from affecting the catalyst performance.

[0057] The present invention is further described below in conjunction with specific examples. In order to further explain the present invention, preferred embodiments of the present invention are described in conjunction with examples, but it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the present invention. In addition, it should be understood that after reading the contents disclosed in the present invention, those skilled in the art may make various changes or modifications to the present invention, and these equivalent forms also fall within the scope of protection defined by the present invention.

[0058] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods; the reagents, materials, etc. used in the following examples, unless otherwise specified, can be obtained from commercial channels. Example

[0059] This example shows a MOF-74@C CF-BT The synthesis method of nano composite carbon material comprises the following steps:

[0060] (1) Prepare 60 ml of DMF-ethanol-ultrapure water (ratio 1:1:1) solution;

[0061] (2) 0.1473 g H4DOBDC and 0.7718 g Ni(NO3)2·6H2O were dissolved in the above solution and then transferred into a 100 ml hydrothermal reactor. After the reaction was completed at 100 °C for 24 h, the reaction was cooled to room temperature. The obtained solid was washed with DMF and methanol three times respectively, and finally vacuum dried at 80 °C for 12 h to obtain Ni-MOF-74.

[0062] (3) Weigh 0.05 g of skin powder and dissolve it in 10 ml of deionized water. Add 10% HCl solution to adjust the pH to 1.5-2.0, and then shake at 40°C for 2 h.

[0063] (4) Weigh 0.05 g MOF-74 and 0.1 g bayberry tannin respectively and dissolve them in the conical flask in step (3), stir them at 40 °C for 30 min with a magnetic stirrer, and then shake them on an oscillator;

[0064] (5) After sufficient shaking, wash with deionized water and anhydrous ethanol 2 to 3 times, filter and dry in an oven at 80°C for 12 h;

[0065] (6) The dried product was placed in a tubular furnace in a nitrogen atmosphere for heat treatment, and then naturally cooled to room temperature to obtain a nano-MOF-74@C constructed with leather powder as a carrier. CF-BT Nanomaterials.

[0066] Figure 1 The MOF-74@C prepared in Example 1 CF-BT The scanning electron microscope image of the material shows that a nanomaterial was synthesized using leather powder as a modification and a metal-organic framework polyphenol supramolecular network as a functional assembly.

[0067] The MOF-74@C obtained in Example 1 CF-BT Phase identification, micromorphology and structure characterization of carbon materials: The prepared materials were identified by powder X-ray diffractometer and X-ray photoelectron spectrometer, and the obtained materials were characterized by micromorphology and structure using scanning electron microscope. As can be seen from the figure, a MOF composite material with a flower-like structure as the center was synthesized.

[0068] Figure 2 : XRD patterns of MOF-74@BT materials obtained at different calcination temperatures (600 ℃, 700 ℃, 800 ℃) in Example 1.

[0069] As can be seen from the figure, the obtained sample is of high purity, with no obvious impurities generated. The sharp diffraction peaks indicate that the synthesized material has good crystallinity. The MOF-74@CCF-BT material has three obvious characteristic diffraction peaks at 2θ=44.5°, 51.8°, and 76.3°, corresponding to the (111), (200), and (220) planes, which are highly matched with the Ni (PDF#65-2865) card.

[0070] Figure 3 The MOF-74@C prepared at 800°C in Example 1 CF-BT Scanning electron microscope image and EDS spectrum of the material. As can be seen from the figure, the flower-like MOF-74 was successfully synthesized as the central carrier, modified by other carbon sources, and the Ni content was very high.

[0071] Figure 4 The MOF-74@C prepared at 800°C in Example 1 CF-BT The elements and spectrum of the material. As can be seen from the figure, the main elements of the material are Ni, C, N, P, and O. Example

[0072] This example shows a MOF-74@C with a flower-like structure as the center CF-BT To study the electrochemical performance of the catalyst.

[0073] The present invention uses a platinum electrode as a counter electrode, a saturated silver chloride electrode (Ag / AgCl) as a reference electrode, and MOF-74@C CF-BT The electrode made of the material is used as the working electrode.

[0074] 4 mg of the catalyst of the present invention was weighed on a scale and dispersed in 1 mL of a mixed solution (235 μL of deionized water, 750 μL of isopropanol and 15 μL of 5 wt% Nafion solution) to prepare a catalyst ink. Then 28 μL of the ink was gradually added dropwise to the surface of the glassy carbon electrode (catalyst loading 0.25 mg cm -2 ), and then the electrocatalytic performance was tested after natural drying.

[0075] All the electrocatalytic performance tests described in the present invention are carried out in 0.1 M KOH (pH = 13.62) electrolyte, and the potential measured in the experiment can be converted to the potential relative to the reversible hydrogen electrode (RHE) by the following formula:

[0076]

[0077] The potential values ​​involved in the present invention are all potentials relative to a reversible hydrogen electrode.

[0078] The catalyst of the present invention needs to be activated by CV for 3 cycles before electrochemical testing.

[0079] The catalysts described in the present invention are all tested at room temperature to prevent large temperature changes from affecting the catalyst performance.

[0080] The Nafion added in the catalyst preparation process of the present invention is produced by Aldrich Sigma Company and has a concentration of 5%.

[0081] Use a pipette to draw 7 ul of the catalyst and drop it onto the working electrode. Wait for it to dry naturally and repeat this step 3 times. Then slowly place the working electrode into the oxygen-saturated 0.1 M KOH electrolyte. In this step, prevent bubbles from forming on the working electrode. Oxygen should be continuously introduced into the electrolyte during the entire test to ensure oxygen saturation.

[0082] The catalyst obtained in this embodiment was subjected to cyclic voltammetry and linear cyclic voltammetry tests: the cyclic voltammetry experiment was carried out using the electrochemical workstation produced by Pine, USA, and the test voltage scanning range was -0.9-0.1 V, and the scanning speed was 50 mV / s. During the test, the current density of 50 mV / s was used to activate it for 3 turns before the cyclic voltammetry test was carried out. The linear cyclic voltammetry test was also carried out using the Pine electrochemical workstation, and the test voltage scanning range was -0.9-0.1 V, and the scanning speed was 50 mV / s. The speed test can obtain the current density of the catalyst material at different speeds, and the number of transferred electrons can be known using the KL equation. The test current density is 10 mV / s, and the speed is 400 rmp, 625 rmp, 900 rmp, 1225 rmp, 1600 rmp, 2025 rmp. Stability and methanol tolerance are also important indicators of catalyst performance. The test was also completed on an electrochemical workstation. The stability test voltage was -0.189 V and the test time was 20,000 s. The methanol tolerance test voltage was -0.189 V and the test time was 1,000 s. 2 mL of methanol solution was dripped in 300 s.

[0083] Figure 5 The MOF-74@C prepared at 800°C calcination temperature in Example 1 CF-BT Cyclic voltammetry characteristic curve of the material at 1600 rpm in 0.1 M KOH saturated with O2 (test voltage scanning range: -0.9-0.1 V, scanning speed: 50 mV / s). As can be seen from the figure, when the test environment is saturated with oxygen, the CV curve under oxygen saturation conditions has an obvious oxygen reduction peak at a potential of 0.71 V (vs. RHE), which indicates that the sample MOF-74@C CF-BTThe material has obvious catalytic activity for oxygen reduction.

[0084] Figure 6 The MOF-74@C prepared by adding different proportions of MOF-74 and bayberry tannin at 800°C in Example 1 CF-BT The LSV comparison of the material at 1600 rmp in 0.1 M KOH saturated with O2 (scanning range is -0.9-0.1 V, scanning rate is 10 mV / s). It can be seen from the figure that when the ratio of MOF-74 is added 0.05 @C CF-BT0.1 The catalytic performance of the sample is the best.

[0085] Figure 7 Pt / C and MOF-74@C prepared at 800 °C in Example 1 CF-BT The LSV comparison of the material at 1600 rpm in O2-saturated 0.1 M KOH (scanning range: -0.9-0.1 V, scanning rate: 10 mV / s) shows that the starting potential of the material is 1.10 V, which is better than that of the Pt / C electrode. The half-slope potential of 0.76 V is slightly lower than that of the Pt / C electrode. However, the material has a larger limiting current density of 6.3 mA cm-2 than that of Pt / C. -2 .

[0086] Figure 8 The MOF-74@C prepared at different calcination temperatures (700 °C, 750 °C, 800 °C) in Example 1 CF-BT LSV comparison of materials at 1600 rpm in 0.1 M KOH saturated with O2 (test voltage range: -0.9-0.1 V, scan rate: 50 mV / s). It can be seen from the figure that when the calcination temperature is 800 °C, MOF-74@C CF-BT Optimal material performance.

[0087] Fig. 9 The best sample MOF-74@C prepared at 800 °C in Example 1 CF-BT Catalyst MOF-74@C was heated at different speeds (400 rpm, 625 rpm, 900 rpm, 1225 rpm, 1600 rpm, 2025 rpm) in 0.1 M KOH saturated with O2. CF-BT The LSV curve (scanning speed: 10 mV / s) shows that with the increase of rotation speed, the limiting current density shows a uniform increasing trend. The ring-disk electrode test shows that the electron transfer number is 3.7, indicating that the reaction process follows a 4-electron mechanism.

[0088] Fig.10The best sample MOF-74@C prepared at 800 °C in Example 1 CF-BT The comparison of the IT curve of commercial Pt / C in O2-saturated 0.1 M KOH at 1600 rpm for a long time. As can be seen from the figure, after 20,000 s of chronoamperometry testing, the initial current density of the commercial Pt / C catalyst obviously lost 23%, while MOF-74@C CF-BT The material loss was 18%, which indicated that the catalyst had better stability than the commercial Pt / C catalyst.

[0089] Using the IT technique, 2 mL of methanol was added to 0.1 M KOH electrolyte at 1600 rpm at 300 s to measure the best sample MOF-74@C prepared at 800 °C in Example 1. CF-BT The methanol tolerance of the commercial 20% Pt / C catalyst is shown in Figure 2. Fig.11 It can be observed from the figure that MOF-74@C CF-BT The limiting current density of MOF-74@C catalyst changed only slightly, while the current density of Pt / C catalyst changed significantly due to methanol oxidation. After running for 700 s, the limiting current density of MOF-74@C catalyst changed significantly. CF-BT The current density still maintains a stable trend, while the Pt / C retention rate decays to below 50%. CF-BT It is superior to Pt / C in terms of methanol tolerance.

[0090] The above is an explanation of the embodiments of the present invention. However, the present invention is not limited to the above embodiments. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a hierarchical porous collagen-based metal nickel organic framework composite carbon nanofiber fuel cell cathode material, characterized in that: The preparation method comprises the following steps: (1) Prepare 60 ml of DMF-ethanol-ultrapure water solution with a volume ratio of 1:1:1; (2) H4DOBDC and Ni(NO3)2·6H2O were dissolved in the above solution, and then transferred into a 100 ml hydrothermal reactor, maintained at a certain temperature, and cooled to room temperature after the reaction was completed for a period of time. The obtained solid was washed with DMF and methanol for three times respectively, and finally vacuum dried under certain conditions to obtain Ni-MOF-74; (3) Weigh the white skin powder and dissolve it in 10 ml of deionized water, add 10% HCl solution to adjust the pH, and then shake it at 40°C for 2 h; (4) Weigh a certain amount of MOF-74 and bayberry tannin (BT) respectively and dissolve them in the conical flask in step (3), stir them with a magnetic stirrer, and then shake them under an oscillator; (5) After sufficient shaking, wash with deionized water and anhydrous ethanol 2 to 3 times, filter and dry in an oven; (6) The dried product was placed in a tubular furnace in a nitrogen atmosphere for heat treatment, and then naturally cooled to room temperature to obtain a hierarchical porous collagen-based metal nickel organic framework composite carbon nanofiber MOF-74@CCF-BT electrode material with collagen fiber as the main component of white skin powder as the substrate and modified by interfacial adhesion of bayberry tannin.

2. The preparation method according to claim 1, characterized in that: In step (2), the temperature of the hydrothermal reaction is 100° C., the time is 24 h, and the temperature of the vacuum drying is 80° C., the time is 12 h.

3. The preparation method according to claim 1, characterized in that: The pH value in step (3) is adjusted to be in the range of 1.5 to 2.

0.

4. The preparation method according to claim 1, characterized in that: In step (4), the magnetic stirring time is 30 min, the oscillator temperature is 40° C., and the time is 2 h.

5. The preparation method according to claim 1, characterized in that: In step (5), the drying temperature is 80° C. and the drying time is 12 h.

6. The preparation method according to claim 1, characterized in that: The heat treatment in step (6) is as follows: heating to 800°C at a heating rate of 5°C / min, maintaining for 2 hours, and then naturally cooling to room temperature.

7. A hierarchical porous collagen-based metal nickel organic framework composite carbon nanofiber MOF-74@CCF-BT fuel cell cathode material prepared by the preparation method according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Preparation method of Fe and N-doped porous carbon nanofiber applicable to cathode catalyst for polymer fuel cell

    CN104289249A

  • Nitrogen-doped carbonized bacterial cellulose-based hierarchical porous carbon composite material and preparation method thereof

    CN110265669A